THE IMPACT OF ONLINE CUSTOMER REVIEWS AND ONLINE CUSTOMER RATINGS TOWARDS PURCHASING INTENTION THROUGH CONSUMER BRAND PERCEPTION AS AN INTERVENING VARIABLE - Andhy Tri Adriyanto; Agus Prasetyo; Sudarmin Sudarmin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The internet cause modern lifestyle underwent immense growth, even more online media has penetrated to the food business. This study aims to determine the impact of online customer review and online customer rating towards purchasing intention through consumer brand perception as an intervening variable. The population of this study was online food customers in Semarang city with 96 respondents. Data was taken from two sources, namely primary data and secondary data. This study used quantitative method. Sample was taken by using non-probability sampling technique with purposive sampling method. The collected data was analyzed using Structural Equation Modeling (SEM) with SmartPLS version 3.2 software. This study obtained several findings. First, online customer review and online customer rating had a significant effect on consumer brand perception. Second, online customer review, online customer rating and consumer brand perception had a significant effect on purchasing intention. The mediation test showed that consumer brand perception variables can mediate between the effects of online customer reviews and online customer ratings on purchasing intention.